PENGARUH KOMPENSASI TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP KINERJA GURU SERTIFIKASI SEKOLAH MENENGAH PERTAMA NEGERI DI KOTA PEKANBARU - ", Sriwahyuni; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Efforts to improve the performance of certification teachers have been anticipated by the Pekanbaru City government by providing additional employee income. However, the provision of additional income which aims to improve teacher performance has decreased every year and is eliminated in 2019. The objectives of this study were to find out: 1) how to provide additional compensation for certification teacher employee income, 2) how the performance of certification teachers and 3) the effect of giving Additional compensation for Employee Income for the performance of State Junior High School certification teachers in Pekanbaru City. This research is a quantitative research using a survey method which was conducted at the State Junior High Schools in Pekanbaru City. The population in this study were 1153 certified teachers in 45 State Junior High Schools in Pekanbaru City. The sampling technique used a two-stage cluster random sampling method with 92 teachers as respondents. Data collection was carried out by distributing questionnaires. After the data was collected, it was analyzed using statistical tests through the SPSS program. The results of the study with the correlation test obtained the value of r count 0.321> r table 0.205 with a significance level of 5%. Because r count is greater than r table, it can be concluded that Ha is accepted and Ho is rejected. So that there is an influence between the provision of additional compensation for employee income on the performance of teachers in State Junior High School certification in Pekanbaru City. The percentage of influence of variable X on variable Y is 10.3% while the remaining 89, 7% is influenced by other variables. The provision of additional compensation for employee income has a low relationship with teacher performance, the closeness of the relationship is in the range 0.200 - 0.399 which is in the low category.  Keywords : Employee Income Additional Compensation, Performance, Teacher Certification